Fly on the wall : how one girl saw everything - Lockhart, E. (New York : Delacorte Press, 2006)
When Gretchen Yee, a student at the Manhattan School for Art and Music, wishes she were a fly on the wall of the boys' locker room, she never expects her wish to come true in such a dramatic way.
2 7 13 19 28
Keywords: Artists -- Fiction; Interpersonal relations -- Fiction; Metamorphosis -- Fiction; Flies -- Fiction; High schools -- Fiction; Schools -- Fiction; New York (N.Y.) -- Fiction